In vivo Characterization of Plasmodium berghei P47 (Pbs47) as a Malaria Transmission-Blocking Vaccine Target - Yenkoidiok-Douti, Lampouguin; Canepa, Gaspar E.; Barletta, Ana Beatriz F.; Barillas-Mury, Carolina (Frontiers in Microbiology, 2020)
An effective vaccine to reduce malaria transmission is central to control and ultimately achieve disease eradication. Recently, we demonstrated that antibodies targeting the Plasmodium falciparum surface protein P47 (Pfs47) reduce parasite transmission to Anopheles gambiae mosquitoes. Here, Plasmodium berghei (Pb) was used as a model to assess the in vivo efficacy of a P47-targeted transmission blocking vaccine (Pbs47). Mice were immunized following a prime/boost regimen and infected with P. berghei. The effect of immunization on infectivity to mosquitoes was evaluated by direct feeding on P. berghei-infected mice. The key region in Pbs47 where antibody binding confers protection was mapped, using a combination of antigen deletions and functional studies, and the immunogenicity of this protective antigen was enhanced by conjugation to a virus-like particle. Passive immunization with purified IgG significantly reduced oocyst numbers in mosquitoes at final serum concentrations of 100 and 50 μg/mL (Transmission-reducing activity of 77 and 67%, respectively), while affinity purified Pbs47-specific rabbit IgG conferred protection at doses as low as 10 and 1μg/mL (Transmission-reducing activity of 88 and 77%, respectively). These studies confirm that P47 is a promising transmission blocking target in vivo and show that antibodies to the same specific region in Pfs47 and Pbs47 confer protection.